ANTI ARTHRITIC ACTIVITY OF TINOSPORA CORDIFOLIA LEAVES BY DENATURATION STUDIES - R. Maheswari, R. Ramya, (International Journal of Innovative Research in Medical Science, 2016)
The study was designed to evaluate the phytochemical screening and anti-arthritic activity of various bark extract of Tinospora cordifolia. The main objective of our study is to evaluate in vitro anti arthritic activity of various bark extracts of Tinospora cordifolia by using BSA denaturation method. Our study displayed that different bark extracts of Tinospora cordifolia (MLE, ELE and CFE) were able to inhibit the protein denaturation and can be used as an anti arthritic agent. The percentage of protein denaturation by different bark extracts of Tinospora cordifolia (MLE, ELE and CFE) were found to be 23%, 36%, 43% (MLE), 19%, 28%, 37% (ELE) and 43%, 58%, 66% (CFE) at concentration 100μg, 250μg and 500μg etc. From the present studied it had been concluded that CFE, and MLE were exhibiting the potential capability to inhibit the denaturation of protein when compared with standard drug diclofenac sodium. The results indicate that the extract contains antioxidants and phytochemicals. Proximate analysis of Tinospora cordifolia showed wide variations but was in compliance to standard monographs. Qualitative analysis of Tinospora cordifolia extracts of stem part showed the presence of alkaloids, carbohydrates, glycosides, phytosterols, tannins, and saponin has found in watery extract.